2005
DOI: 10.1016/j.aap.2004.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of practice, age, and task demands, on interference from a phone task while driving

Abstract: Experimental research on the effects of cellular phone conversations on driving indicates that the phone task interferes with many drivingrelated functions, especially with older drivers. Unfortunately in past research (1) the dual task conditions were not repeated in order to test for learning, (2) the 'phone tasks' were not representative of real conversations, and (3) most often both the driving and the phone tasks were experimenter-paced. In real driving drivers learn to time-share various tasks, they can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
105
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(121 citation statements)
references
References 13 publications
10
105
1
5
Order By: Relevance
“…The take-over of vehicle control can be critical if the automated driving system is operated in an unfamiliar, unexpected or unstructured environment, situation or condition, because then the situation's demand may exceed the capacity for reacting since such situations have an increased demand (Shinar, Tractinsky, & Compton, 2005;Wagner & Koopman, 2015). For example, Payre, Cestac, and Delhomme (2016) found a higher take-over time with increasing trust in an emergency situation if training was insufficient.…”
Section: The Role Of Trust In Automated Drivingmentioning
confidence: 99%
“…The take-over of vehicle control can be critical if the automated driving system is operated in an unfamiliar, unexpected or unstructured environment, situation or condition, because then the situation's demand may exceed the capacity for reacting since such situations have an increased demand (Shinar, Tractinsky, & Compton, 2005;Wagner & Koopman, 2015). For example, Payre, Cestac, and Delhomme (2016) found a higher take-over time with increasing trust in an emergency situation if training was insufficient.…”
Section: The Role Of Trust In Automated Drivingmentioning
confidence: 99%
“…The motivation for such legislation may initially have been concern about interference caused by holding and dialing a cellular phone, and early studies suggested that the manual aspects of cellular phone use were the critical determinant of a decrement in driving performance (Drory, 1985). However, recent behavioral studies have shown that simulated driving performance is also disrupted by conversations using hands-free devices Nilsson, 1994, 1995;Anttila and Luoma 2005;Beede and Kass, 2006;Brookhuis et al, 1991;Consiglio et al, 2003;Horberry et al, 2006;Hunton and Rose, 2005;Jamson and Merat 2005;Lamble et al, 1999;Levy et al, 2006;Liu and Lee, 2005;Matthews et al, 2003;Patten et al, 2004;Ranney et al, 2005;Shinar et al, 2005;Strayer and Drews, 2004;Strayer et al, 2003Strayer et al, , 2006Strayer and Johnston, 2001;Bolling, 2005, 2006;Treffner and Barrett, 2004), and epidemiological studies of real-world accidents suggest that users of hands-free phones are just as likely to have an accident as users of hand-held devices (Redelmeier and Tibshirani, 1997;McEvoy et al, 2005). In their meta-analysis of recent dual-task driving studies, Horey and Wickens (2006) concluded that the costs to driving performance resulting from a secondary simulated conversation task were equivalent for hand-held and hands-free devices.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, multitasking of driving and conversing on a cell phone is technologically available, but intuitively seems dangerous in some circumstances. Although driving becomes sufficiently cognitively automated (Schneider, 1999) to permit experienced drivers to perform other tasks at the same time, such as carrying on a conversation, a large number of behavioral studies have now shown that performing another cognitive task while driving an actual or virtual car substantially degrades driving performance Nilsson, 1994, 1995;Anttila and Luoma, 2005;Beede and Kass, 2006;Brookhuis et al, 1991;Consiglio et al, 2003;Drory, 1985;Engström et al, 2005;Haigney et al, 2000;Hancock et al, 2003;Horberry et al, 2006;Horrey and Wickens, 2004;Hunton and Rose, 2005;Jamson and Merat, 2005;Kubose et al, 2006;Lamble et al, 1999;Lesch and Hancock, 2004;Liu and Lee, 2005;Matthews et al, 2003;McKnight and McKnight, 1993;Patten et al, 2004;Ranney et al, 2005; Nunes, 2000, 2003;Santos et al, 2005;Shinar et al, 2005; Drews, 2004, 2007;Strayer et al, 2003Strayer et al, , 2006Strayer and Johnston, 2001; Bolling, 2005, 2006;Treffner and Barrett, 2004). Although some of these studies show that some aspects of driving are unaffected by a secondary task (e.g., Haigney et al, 2000) and in some cases certain aspects improve (e.g., Brookhuis et al, 1991;Engström et al, 2005), a recent meta-analysis of the literature suggests a large overall decrement in driving performance when a secondary task is added (Horey and Wickens, 2006).…”
mentioning
confidence: 99%
“…Only one previous study has examined the longer-term effects of in-vehicle distraction. Shinar, Tractinsky, and Compton (2005) found that drivers became more proficient in vehicle control measures while conversing on a cellular phone over repeated trials. Meta-analyses of cell phone conversation studies have shown that lateral and longitudinal vehicle control measures are less affected by the presence of in-vehicle distractors (Caird et al, 2004;Horrey & Wickens, 2006).…”
Section: Introductionmentioning
confidence: 99%